Pengaruh efikasi diri dan dukungan sosial teman sebaya terhadap prestasi belajar - Syahrudin Syahrudin (Cognicia, 2019)
Learning achievement is influenced by several factors such as internal factors or external factors. The purpose of this study is to determine the effect of self-efficacy and social support of peers on learning achievement simultaneously or together. The sampling technique uses simple random sampling in one of the existing SMA N in Woha District, Bima Regency, West Nusa Tenggara. The subjects in this study were 150 high school students in class X. The method of data collection in this study uses a scale of self-efficacy and social support of peers and reporr cards. The results of the multiple regression test analysis showed that self-efficacy and social support of peers simultaneously or simultaneously affect the learning achievement with an influence contribution of 25,0%.